Time fractional super KdV equation: Lie point symmetries, conservation laws, explicit solutions with convergence analysis - Gulsen, Selahattin; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2022)
In this work, one-point Lie symmetry method is applied to time fractional super KdV equation in order to obtain similarity variables and similarity transformations with Riemann-Liouville derivative. These transformations reduce the governing equation to an ordinary differential equation of fractional order. A new and effective conservation theorem based on Noether's theorem is used to obtain conserved vectors. Then, we construct power series solutions for the reduced time fractional ordinary differential equation and prove that the solutions are convergent. Lastly, some interesting graphs are given to explain physical behaviors.
Keywords: Lie point symmetries; super KdV equation; power series solutions; conserved vectors